Photosynthetic properties of Quercus × hispanica Lam. and Q. suber L. under harsh Central European winter conditions - Holland, V.; Brüggemann, W. (Photosynthetica, 2011)
In search for new forestation tree species for future Central European climate conditions, Mediterranean evergreen oak taxa are investigated for their summer drought- and winter frost-hardiness. Here we report on the winter performance of the photosynthetic apparatus of Quercus × hispanica Lam. and its evergreen parental species Q. suber L. under extraordinary harsh winter conditions. Both taxa showed a strong decline of photosystem II (PSII) quantum efficiency (Fv/Fm) with a concomitant increase in the deepoxidation state (DES) of the xanthophyll pigments depending on (severe) frost events during winter, and these parameters significantly correlated with minimum air temperatures during periods of chronic photoinhibition at mid-winter, but not at the onset of winter in response to the first frost nights. Fv/Fm and DES correlated with each other in both taxa throughout the winter.
Keywords: evergreen; frost stress; oak; photoinhibition; xanthophyll cycle

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana, Javier (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Effects of winter cold stress on photosynthesis and photochemical efficiency of PSII of the Mediterranean Cistus albidus L. and Quercus ilex L. - Oliveira, G.; Penuelas, J. (Plant Ecology, 2005)
Keywords: evergreen; Fv/Fm; Mediterranean winter; photoinhibition; semi-deciduous

Effects of winter cold stress on photosynthesis and photochemical efficiency of PSII of the Mediterranean Cistus albidus L. and Quercus ilex L. - Oliveira, G; Penuelas, J (Plant Ecology, 2004)
This study examined the photosynthetic and growth performances of potted plants of Cistus albidus L. and Quercus ilex L. submitted either to natural Mediterranean winter conditions or to mild greenhouse conditions. Plants grown outdoors exhibited lower light and CO2 -saturated CO2 assimilation rates Asat and apparent quantum yield i than those indoors. Until mid-winter, C. albidus had higher Asat than Q. ilex, but differences disappeared after a period of severe cold. Maximal photochemical efficiency of PSII Fv/Fm measured predawn was higher in C. albidus than in Q. ilex, and decreased throughout the season in outdoor plants. Fv/Fm also decreased at light saturation Asat in both species. Fv/Fm was correlated with photosynthetic capacity and efficiency quantum yield, but the resulting regression slopes were different between the two species. At the physiological level, C. albidus seemed to cope better with cold stress than Q. ilex. However, winter stress induced reduction of leaf absorptance, increased leaf mass per area, extensive leaf damage and high plant mortality in C. albidus. This suggests that the high performance of C. albidus leaves is not likely to be maintained for long periods of cold stress, and may therefore depend on continuous leaf replacement. Quercus ilex showed a conservative behaviour, with low net assimilation rates but greater leaf and plant survival than C. albidus.
Keywords: evergreen; Fv/Fm; Mediterranean winter; photoinhibition; semi-deciduous

Effects of tension wood on specific conductivity and vulnerability to embolism of Quercus ilex seedlings grown at two atmospheric CO2 concentrations - Gartner, Barbara L; Roy, Jacques; Huc, Roland (Tree Physiology, 2003)
To determine whether there are decreases in hydraulic function of a woody stem when it has increased mechanical loading, Quercus ilex L. seedlings were grown upright or inclined to force the production of large amounts of tension wood (TW). Seedlings were grown in ambient or elevated carbon dioxide concentrations ([CO2]) for 16–17 months to provide two sets of seedlings differing in growth rates and allocation patterns. In both CO2 environments, inclination caused formation of large amounts of TW at the base and mid-section of most stems, but not at the stem tips. Contrary to expectation, there were no significant effects of stem inclination or amount of TW on specific conductivity (ks) or vulnerability to embolism. Samples with high amounts of TW had higher vessel frequency, similar average vessel lumen area, similar vessel lumen fraction (6% of the transverse area), elevated frequency of vessels in the smallest diameter class, and higher wood density than samples with very little TW. Samples from seedlings in the elevated [CO2] treatment had similar vessel frequency, larger average vessel lumen area (caused by a higher frequency of large-diameter vessels), similar vessel lumen fraction, and similar wood density as samples from seedlings in the ambient [CO2] treatment. There was a strong position effect: the highest wood density and lowest ks were at the stem base, intermediate values were at the middle, and the lowest density and highest ks were at the stem tip. We conclude that, in a species that uses different cells for mechanical support and water transport, there can be large modifications in performance of the mechanical function through TW formation without impacting the water transport functions—ks and vulnerability to embolism.
10.1093/treephys/23.6.387
Keywords: ecological wood anatomy; evergreen; hydraulic architecture; Mediterranean; structure/function relationship

Effects of tension wood on specific conductivity and vulnerability to embolism of Quercus ilex seedlings grown at two atmospheric CO2 concentrations - Gartner, Barbara L.; Roy, Jacques; Huc, Roland (Tree Physiology, 2003)
To determine whether there are decreases in hydraulic function of a woody stem when it has increased mechanical loading, Quercus ilex L. seedlings were grown upright or inclined to force the production of large amounts of tension wood (TW). Seedlings were grown in ambient or elevated carbon dioxide concentrations ([CO2]) for 16–17 months to provide two sets of seedlings differing in growth rates and allocation patterns. In both CO2 environments, inclination caused formation of large amounts of TW at the base and mid-section of most stems, but not at the stem tips. Contrary to expectation, there were no significant effects of stem inclination or amount of TW on specific conductivity (ks) or vulnerability to embolism. Samples with high amounts of TW had higher vessel frequency, similar average vessel lumen area, similar vessel lumen fraction (6% of the transverse area), elevated frequency of vessels in the smallest diameter class, and higher wood density than samples with very little TW. Samples from seedlings in the elevated [CO2] treatment had similar vessel frequency, larger average vessel lumen area (caused by a higher frequency of large-diameter vessels), similar vessel lumen fraction, and similar wood density as samples from seedlings in the ambient [CO2] treatment. There was a strong position effect: the highest wood density and lowest ks were at the stem base, intermediate values were at the middle, and the lowest density and highest ks were at the stem tip. We conclude that, in a species that uses different cells for mechanical support and water transport, there can be large modifications in performance of the mechanical function through TW formation without impacting the water transport functions—ks and vulnerability to embolism.
10.1093/treephys/23.6.38710.1093/treephys/23.6.387
Keywords: ecological wood anatomy; evergreen; hydraulic architecture; Mediterranean; structure/function relationship

Comparative protective strategies of Cistus albidus and Quercus ilex facing photoinhibitory winter conditions - Oliveira, G; Penuelas, J (Environmental and experimental botany, 2002)
The role of structural photoprotection under photoinhibitory winter conditions was evaluated in two Mediterranean woody species: Cistus albidus (semideciduous) and Quercus ilex (evergreen). Shoots were manipulated in order to modify the light load naturally received by the leaves throughout the cold season, and monitored for changes in maximum photochemical efﬁciency of PSII, phenology, and leaf morphology. Naturally steep leaves of C. albidus were restrained to a horizontal position, and compared with control leaves (naturally horizontal, or steeply inclined). Fully exposed leaves of Q. ilex were artiﬁcially protected through partial shading, and compared with control leaves (not shaded). During the cold season, the most exposed (either naturally or artiﬁcially) leaves were always more photoinhibited (had lower maximal photochemical efﬁciency of PSII) than the photoprotected ones. The differences disappeared at the beginning of spring. Winter photoinhibition was not more pronounced in older than in younger leaves of C. albidus, indicating that inclination rather than age affected their photochemical efﬁciency. Leaf chlorophyll contents were not signiﬁcantly affected by the manipulations. Leaf thickness decreased slightly in the least exposed shoots of the evergreen species, but no changes were detected in leaf morphological traits of the semideciduous one. The increased photoinhibitory pressure led only to slight and non-signiﬁcant changes in phenology and growth
Keywords: evergreen; leaf angle; manipulation; Mediterranean winter; photoprotection; semideciduous

Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. - Gulías, J; Flexas, J; Abadía, A; Madrano, H (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]
Keywords: chlorophyll fluorescence; deciduous; Drought; evergreen; Gas exchange; leaf mass area; nitrogen; Pistacia; Quercus; Rhamnus; xanthophyll cycle

Évolution du potentiel hydrique foliaire et de la conductance stomatique de quatre chênes méditerranéens lors d'une période de dessèchement - Acherar, M; Rambal, S; Lepart, J (Ann. For. Sci., 1991)
Influence of soil drying on leaf water potential and stomatal conductance in four Mediterranean oak species. The water relations and the responses of 2 evergreen Quercus species (Quercus ilex L and Q suber L) and 2 deciduous species (Q afares Pomel and Q faginea Willd) were studied under experimental conditions. Two-yr old seedlings grown in 30-1 pots were subjected to a drying period where stomatal conductance, pre-dawn leaf water potential and minimum leaf water potential were measured. The results show that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al (1978, 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance (gsr max) as described by the reciprocal function gsr max = (-0.47 + 2.61 ψb)-1 for the evergreen oaks and gsr max = (-1.94 + 7.39 ψb)-1 for the deciduous ones. The differences between the 2 groups may partially explain their geographic distributions, and also lead to general questions concerning the mechanisms of water use in the Mediterranean oak species.
Keywords: deciduous; evergreen; mediterranean species; Quercus; Stomatal conductance; water potential; water stress